2006
DOI: 10.1590/s0066-782x2006000600005
|View full text |Cite
|
Sign up to set email alerts
|

Critérios ecocardiográficos para definição de graus de disfunção ventricular em ratos portadores de estenose aórtica

Abstract: M a i l i n d A d d r e s s : K a t a s h i O k o s h i• T r a v e s s a C y r o T a r g a , 1 1 5 -1 8 6 1 0 -2 5 0 -B o t u c a t u , S P -B r a z i l E-mail: okoshi@cardiol. OBJECTIVEThe purpose of this study was to identify echocardiographic parameters that allow distinguishing different levels of cardiac dysfunction in aortic banded rats. METHODSWistar male rats (90-100 g) were subjected to aortic banding (n=23) or a sham operation (n=12). The following echocardiographic parameters were evaluated and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…When normalized to body weight, LV diastolic diameter and left atrium diameter were higher in SHR-DM than SHR. Normalization of cardiac structural parameters to body weight can lead to misinterpretation of results as cardiac chambers diameters are not exactly proportional to body weight [41]. Therefore, our data suggest that DM increases LV systolic diameter without dilating LV or left atrium in spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 89%
“…When normalized to body weight, LV diastolic diameter and left atrium diameter were higher in SHR-DM than SHR. Normalization of cardiac structural parameters to body weight can lead to misinterpretation of results as cardiac chambers diameters are not exactly proportional to body weight [41]. Therefore, our data suggest that DM increases LV systolic diameter without dilating LV or left atrium in spontaneously hypertensive rats.…”
Section: Discussionmentioning
confidence: 89%
“…Meanwhile, Sullivan et al [31] observed significant improvement in physical performance in patients aged 40-75 years who had CHF treated with a digoxin dose of 0.25 mg/day. Morisco et al [23] evaluated 10 patients with CHF treated for 3 weeks with digoxin at a dosage of 0.25 mg/kg and found some improvements in the exercise capacity of the patients studied. This difference in the results may be related to the drug dosage, type of stress, and clinical conditions of the individuals tested, because digoxin may be more sensitive to heart failure conditions.…”
Section: (N = 8) Digo (N = 8) T (N = 8) Tdigo (N = 8)mentioning
confidence: 99%
“…These periods are suitable to observing morphological and functional alterations in rats with SVA and precede appearance of HF, which takes place around the 20 th week 9,10,13 .…”
Section: Animals and Experimental Protocolmentioning
confidence: 99%
“…Heart's function and structure were analyzed by means of ECHO according to methodology used in our lab 4,9,10,14 . Animals were anesthetized with ketamine chloride (50 mg/kg) and xylazine chloride (1 mg/kg), intraperitoneal.…”
Section: Echocardiographic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation